SERVICE QUALITY, RELIGIOSITY AND CUSTOMER SATISFACTION IMPACTS ON ZAKAT CUSTOMERS’ TRUST IN MALAYSIA : A PILOT STUDY - Syarifah Md Yusof; Abidah Ab Kadir; Nor Aina Mhd Khotib (Jurnal Penyelidikan Sains Sosial, 2023)
It is quite unsettling that the Muslim community has such little faith in the zakat institution . The objective of this pilot study was to develop and establish the psychometric properties of validity and reliability for elements that affect the degree of Muslim community’s trust in zakat institutions. The five SERVQUAL dimensions (tangible, reliable, responsiveness, assurance and empathy), customer satisfaction, and customer trust were factors for this study. The research methodology involved determination of the study sample, formation of research instrument and research procedures that were carried out. There were 30 Muslim communities for the study sample in Malaysia. Convenience sampling was used to choose study participants. Thestudy results showed that reliability coefficient for all variables was high, ranging from 0.78 (assurance dimension) to 0.96 (customer trust).